Delivering green streets: an exploration of changing perceptions and behaviours over time around bioswales in Portland, Oregon - Everett, G.; Lamond, J.E.; Morzillo, A.T.; Matsler, A.M.; Chan, F.K.S. (Wiley, 2018)
Green Infrastructure (GI) is an increasingly popular means of dealing with flooding and water quality issues worldwide. This study examines public perceptions of, and behaviour around, bioswales, which are a popular GI facility in the United States. Bioswales are highly visible interventions requiring support from residents and policy‐makers to be implemented and maintained appropriately. To understand how the residents' perceptions and attitudes might develop over time, we interviewed residents of Portland, Oregon, living near bioswales installed 1–2, 4–5 and 8–9 years ago, to determine awareness, understanding, and opinions about the devices. We found no consistent patterns across time periods, but did find common issues affecting residents' appreciation and acceptance: environmental attitudes, awareness and understanding of purpose and function, plant choice and maintenance, and mess and littering. It was apparent that increased public engagement, localised maintenance strategies, and possibly even customising facilities to meet residents' needs where feasible, might improve acceptance.